Terrorism and child mortality - Daniel Meierrieks; Max Schaub (Health Economics, 2024)
How does terrorism affect child mortality? We use geo-coded data on terrorism and spatially disaggregated data on child mortality to study the relationship between both variables for 52 African countries between 2000 and 2017 at the 0.5~~0.5° grid level. Our estimates suggest that moderate increases in terrorism are linked to several thousand additional annual deaths of children under the age of five. A panel event-study points to economic effects that are larger and compound over time. Interrogating our data, we show that the direct impact of terrorism tends to be very small. Instead, we theorize that terrorism causes child mortality primarily by triggering adverse behavioral responses by parents, medical workers, and policymakers. We provide tentative evidence in support of this argument.
Keywords: 330; Africa; child mortality; panel event-study; terrorism